AGRICULTURAL LAND POTENCIAL AND ENVIRONMENTAL FRAGILITY OF THE CAMPESTRE WATERSHED, COLOMBO - PR - SOARES, Marcia Regina Gomes de Jesus; MELLEK, Jose Elias; ORRUTÉA, Alessandro Góis; KUMMER, Larissa; NUNES, Tiago; BARROS, Yara Jurema de; ANDRETTA, Ronei; FAVARETTO, Nerilde; SOUZA, Luiz Cláudio de Paula (Scientia Agraria, 2008)
The use of the land according to its capability is critical in the implementation of agricultural systems based on environmental sustainability. In this sense, this work aims to apply and compare the systems agricultural suitability of the land (SAA), Ability to Use (SCU) and Environmental Fragility (FA) together with the Environmental Law (APP) in the Campestre watershed located in the Colombo – PR, Brazil, to determine their potential for agricultural use. These methods can be utilized for evaluation and planning of the appropriate use of land for production purposes and environmental preservation. The software SPRING elaborated by the INPE, specifically the LEGAL tool was the base for the maps elaboration. The conflict of use indicates that only 15% of watershed, average between systems of agricultural skills and ability to use the land, is super used, and that approximately 50% of the area is in line with the recommendation. This study also showed that 15% of watershed must be preserved with riparian forest and that 26% of this area of permanent preservation must be restored to meet environmental legislation The results of environmental fragility (potential and emerging) show that the watershed has naturally conducive to a potential degradation due to the high slope of the region and the soil insufficiently developed. However, vegetation in this watershed (43% of natural trees, 17% of trees planted and 25% of pasture) contributes in a positive way reducing the environmental fragility.